Pretreatment Affects Profits From Xylanase During Enzymatic Saccharification of Corn Stover Through Changing the Interaction Between Lignin and Xylanase Protein - Feng, Xiaoting; Yao, Yini; Xu, Nuo; Jia, Hexue; Li, Xuezhi; Zhao, Jian; Chen, Shicheng; Qu, Yinbo (Frontiers in Microbiology, 2021)
Effective pretreatment is vital to improve the biomass conversion efficiency, which often requires the addition of xylanase as an accessory enzyme to enhance enzymatic saccharification of corn stover. In this study, we investigated the effect of two sophisticated pretreatment methods including ammonium sulfite (AS) and steam explosion (SE) on the xylanase profits involved in enzymatic hydrolysis of corn stover. We further explored the interactions between lignin and xylanase Xyn10A protein. Our results showed that the conversion rates of glucan and xylan in corn stover by AS pretreatment were higher by Xyn10A supplementation than that by SE pretreatment. Compared to the lignin from SE pretreated corn stover, the lignin from AS pretreated corn stover had a lower Xyn10A initial adsorption velocity (13.56 mg/g min vs. 10.89 mg/g min), adsorption capacity (49.46 mg/g lignin vs. 27.42 mg/g lignin), and weakened binding strength (310.6 L/g vs. 215.9 L/g). Our study demonstrated the low absolute zeta potential and strong hydrophilicity of the lignin may partly account for relative weak interaction between xylanase protein and lignin from AS pretreated corn stover. In conclusion, our results suggested AS pretreatment weakened the inhibition of lignin to enzyme, promoted the enzymatic hydrolysis of corn stover and decreased the cost of enzyme in bioconversion.